(untitled) (River Edge, NJ, 2003)
This important proceedings volume highlights the major scientific achievement of the last decade in atomic physics, namely the creation of the gaseous Bose-Einstein condensate, which was featured prominently at the XVIII International Conference on Atomic Physics (ICAP2002). Two recipients of the 2001 Nobel Prize delivered lectures at the meeting. Among the topics discussed were novel processes leading to degenerate Fermi gases in atom traps, creation of cold molecules, condensates in optical lattices, atoms in intense fields, tests of fundamental symmetries, quantum control and information, time and frequency standards.
Keywords: Atoms,Nuclear physics